Adsorption kinetic and mechanism of reactive dye on cotton yarns with different wettability in siloxane non-aqueous medium. Issue 7 (2nd July 2020) - Pei, Liujun; Liu, Juanjuan; Gu, Xiaomin; Wang, Jiping
Abstract: Adsorption kinetic of reactive dye (red 195 and blue 19) on cotton yarns with different wettability was compared via a pseudo-first-order kinetic model and a pseudo-second-order kinetic model in siloxane non-aqueous dyeing system and traditional water base. The results shown that the adsorption kinetic of these two dyes could be described by the pseudo-second-order kinetic model. In siloxane non-aqueous dyeing system, the dyeing rate of dye was increased with the increase of yarn wettability, but the final uptake of dye was kept unchanged (close to 20 mg/g). Most remarkably, the final uptake of dye was more than doubled in the siloxane medium comparing with the traditional water bath dyeing, while the half-dyeing time of dye was decreased significantly. Although dyeing rates were increased with temperature for both systems, the final uptake of dyes remained stable with the temperature increase in the siloxane non-aqueous dyeing system but was significantly decreased in traditional water bath. The adsorption mechanism was also discussed, and the medium effects were considered to be important factors in the adsorption of reactive dye. Since reactive dye is completely non-miscible with siloxane medium, but has strong affinity to cotton yarn, almost all of reactive dye will be transferred to yarn surface under mechanical force. As a result, siloxane medium provides an innovative approach to increase dye uptake under a low dyeing temperature (20 °C). Furthermore, reactive dyeing in siloxane non-aqueous system only need a small amount of water without using any salt, and reduce dyeing waste-water emission.